Determinants of Taxpayer Compliance in the Implementation of the Coretax System - Kadek Yoga Suartika; Ni Kadek Sinarwati; Lucy Sri Musmini (Jurnal Riset Perpajakan: Amnesty, 2026)
Taxpayer compliance is a fundamental factor in ensuring sustainable government revenue, particularly in the era of digital tax administration. The rapid development of information technology has encouraged tax authorities to modernize administrative systems to improve efficiency, transparency, and service quality. In Indonesia, the Directorate General of Taxes has implemented the Core Tax Administration System (Coretax) as an integrated digital platform designed to simplify tax administration processes. However, the effectiveness of this system largely depends on taxpayers’ acceptance of technology and their understanding of taxation. Therefore, this study aims to examine the effect of perceived ease of use, perceived usefulness, and tax knowledge on taxpayer compliance in the implementation of the Coretax system. This study employed a quantitative research approach using primary data collected through questionnaires distributed to 150 individual taxpayers selected using purposive sampling. The data were analyzed using multiple linear regression analysis with the assistance of SPSS software. The results indicate that perceived ease of use, perceived usefulness, and tax knowledge have positive and significant effects on taxpayer compliance. Among these variables, tax knowledge demonstrates the strongest influence on compliance behavior. These findings suggest that taxpayer compliance in the digital era is influenced not only by technological aspects but also by taxpayers’ understanding of tax regulations and procedures. This study contributes to the development of the Technology Acceptance Model in the context of digital tax administration and provides practical implications for tax authorities in improving system usability, perceived benefits, and tax education programs to enhance taxpayer compliance.